Identification of LC-HRMS nontarget signals in groundwater after source related prioritization. (15th May 2021) - Kiefer, Karin; Du, Letian; Singer, Heinz; Hollender, Juliane
Highlights: Anthropogenic influence on groundwater samples determined by 498 quantified targets. 6504 LC-HRMS signals in 60 groundwater samples were related to potential sources. Automatic structure annotation of most intense signals from potential urban sources. 12 nontargets and 11 suspects unequivocally identified, 17 tentative candidates. Abstract: Groundwater is a major drinking water resource but its quality with regard to organic micropollutants (MPs) is insufficiently assessed. Therefore, we aimed to investigate Swiss groundwater more comprehensively using liquid chromatography high-resolution tandem mass spectrometry (LC-HRMS/MS). First, samples from 60 sites were classified as having high or low urban or agricultural influence based on 498 target compounds associated with either urban or agricultural sources. Second, all LC-HRMS signals were related to their potential origin (urban, urban and agricultural, agricultural, or not classifiable) based on their occurrence and intensity in the classified samples. A considerable fraction of estimated concentrations associated with urban and/or agricultural sources could not be explained by the 139 detected targets. The most intense nontarget signals were automatically annotated with structure proposals using MetFrag and SIRIUS4/CSI:FingerID with a list of >988, 000 compounds. Additionally, suspect screening was performed for 1162 compounds with predicted high groundwater mobility from primarily urban sources. Finally, 12 nontargets and 11 suspects were identified unequivocally (Level 1), while 17 further compounds were tentatively identified (Level 2a/3). amongst these were 13 pollutants thus far not reported in groundwater, such as: the industrial chemicals 2, 5-dichlorobenzenesulfonic acid (19 detections, up to 100 ng L −1 ), phenylphosponic acid (10 detections, up to 50 ng L −1 ), triisopropanolamine borate (2 detections, up to 40 ng L −1 ), O-des[2-aminoethyl]-O-carboxymethyl dehydroamlodipine, a transformation product (TP) of the blood pressure regulator amlodipine (17 detections), and the TP SYN542490 of the herbicide metolachlor (Level 3, 33 detections, estimated concentrations up to 100–500 ng L −1 ). One monitoring site was far more contaminated than other sites based on estimated total concentrations of potential MPs, which was supported by the elucidation of site-specific nontarget signals such as the carcinogen chlorendic acid, and various naphthalenedisulfonic acids. Many compounds remained unknown, but overall, source related prioritisation proved an effective approach to support identification of compounds in groundwater. Graphical abstract: Image, graphical abstract